Juridical Review of Hospitals Without Supervisory Boards Based on Laws and Regulations - Isfihan, Emirlad; Nugraheni, Ninis; asmuni (JILPR Journal Indonesia Law and Policy Review, 2023)
Hospitals in improving service quality must have autonomy, hospitals are one form of public service reform so that public services can improve. Therefore, in an effort to improve hospital performance, it is necessary to provide guidance and supervision through the establishment of a Supervisory Board. The purpose of this study is to analyse the urgency of establishing a hospital supervisory board and the legal consequences for hospitals that do not have a supervisory board by using normative research methods and using statutory and conceptual approaches. In accordance with statutory provisions, hospitals that do not have a supervisory board do not violate statutory provisions as long as they do not fulfil the criteria required to form a supervisory board. However, legal protection of patients for hospitals that do not have a supervisory board must be guaranteed by the government through supervisory efforts by external supervisors and other stakeholders.